Attitudes and Approaches of Believers and Non-believers among Pedagogy Students from Poland, the Czech Republic and Slovakia Towards LGBT People – a Comparative Analysis - Ryszawy, Sylwia (Studia socjologiczne, 2025)
The article presents the results of a survey conducted among 314 pedagogy (i.e. educational studies) students from Poland, the Czech Republic and Slovakia. Its goal was to learn about attitudes and approaches towards LGBT people of believers and non- believers among students. The choice of these three countries was deliberate due to their different levels of religiosity. The study was conducted using the diagnostic survey method.The results of the survey analysis showed significant differences in attitudes towards LGBT people depending on the respondents’ faith. The level of acceptance of LGBT people is higher among non-believers than among believers. The respondents are most accepting of lesbians and gays, but less accepting of transgender people. Both the general attitude towards LGBT people and the general attitude towards the rights of homosexual people were higher in the group of non-believers. The non-believers were also more likely to declare that homosexuality is normal and should be tolerated.